EFFECT OF EDUCATION LEVEL AND WORK CLIMATE ON PERFORMANCE OF EMPLOYEES AGENCY OF REGIONAL SERVICES IN WEST SUMATRA PROVINCE - Salman M Noer; Reni Respita; Dessyta Gumanti (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
The research is based on the performance of the Staff Officer of the Officials Agency of West Sumatra Province. (2) The influence of work climate on the performance of civil servants of the province of western Sumatra (3) the influence of education and work climate on the performance of civil servants of the Provincial Personnel Board of West Sumatra. The type of this research is Field Research and descriptive. The population of this study is all employees of the Regional Personnel Board of West Sumatra Province as much as 87. Sampling technique with total sampling with a total sample of 30 people. Data collection techniques by spreading questionnaires and documentation, while data analysis used is descriptive analysis and multiple regression analysis. From the results of the study found that the level of education has a significant effect and the work climate on the performance of Personnel Agency Personnel West Sumatra Province has a significant effect. With coefficient of determination equal to a = 0.05% found that tcount> ttable is 6,213> 2,000, Test Result gives interpretation that significance. Based on the results of the study, it can be concluded that the Education and Climate Level significantly influences the performance of civil service personnel of West Sumatra Province. Where the influence of employee variables while the work climate influence by other factors that affect employee performance.